Imidazolyl MOF material as well as preparation method and application thereof

Through the nanospherical amorphous structure of imidazolyl MOF materials, the problem of insufficient electrochemical performance in lithium-ion batteries is solved, and higher electrochemical performance and stability is achieved, the preparation process is simplified, and suitable for Lithium ion battery negative electrode.

CN119306960APending Publication Date: 2025-01-14CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310859681.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-13
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

When used in lithium-ion batteries, existing MOF materials have fewer morphology and larger sizes, resulting in smaller specific surfaces, longer ion diffusion paths, and complex preparation methods, making it difficult to improve electrochemical performance.

Method used

Using imidazolyl MOF material, amorphous structure MOF material with nanospherical morphology is prepared by static reaction method. It has a close-packed structure composed of spherical particles of 50-120nm, and a spherical particle assembled, which simplifies the preparation process and is suitable for lithium ions. Battery negative pole.

Benefits of technology

It improves the electrochemical performance of the negative electrode of lithium-ion battery, including mass specific capacity, rate performance and stability, provides a larger specific surface and a shorter ion diffusion path, alleviates microscopic volume expansion, and is simple in process and green in environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306960A_ABST
    Figure CN119306960A_ABST
Patent Text Reader

Abstract

The invention relates to the field of preparation of MOF (Metal Organic Framework) materials, and discloses an imidazolyl MOF material as well as a preparation method and application thereof. The invention relates to an imidazolyl MOF (Metal Organic Framework) material. The MOF material has a nano spherical shape; the MOF material has an amorphous structure. The imidazolyl MOF material disclosed by the invention is applied to a lithium ion battery, and the electrochemical performance of a negative electrode material is favorably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of preparation of MOF materials, and in particular to an imidazole-based MOF material and a preparation method and application thereof. Background Art

[0002] The energy and environmental problems in the 21st century are becoming increasingly severe, which is an important challenge facing mankind now and in the future. Therefore, it is urgent to develop clean, renewable green new energy, such as wind energy, solar energy, nuclear energy and hydrogen energy, etc. In order to better develop and utilize these new energy sources, it is necessary to develop corresponding new energy storage and conversion devices, and the research and development of new materials that are compatible with them is equally important.

[0003] New lithium-ion batteries, lithium-sulfur batteries, supercapacitors, fuel cells, and water electrolysis devices need to obtain excellent electrochemical properties. The key is to develop efficient electrode materials. Generally speaking, the electrochemical performance can be improved by nano-sizing the electrode materials and rationally designing their composition and structure. Designing and synthesizing some novel nanostructures, such as metal and carbon composite structures, novel hollow nanostructures, multi-metal uniform doping, and heterogeneous structures, can bring about advantages such as fast electron and ion transport, fast mass transfer, alleviated volume expansion, increased active area and sites, and optimized electronic structure. One of the important strategies to achieve the above synthesis is to use metal-organic framework (MOFs) materials as self-templates for subsequent related synthesis designs.

[0004] MOF materials are periodically coordinated crystalline materials formed by self-assembly of transition metal ions and organic ligands. They have the advantages of high porosity, low density, large specific surface area, regular pores, adjustable pore size, and topological structure diversity, and can be used as one of the ideal self-template materials. The nanomaterials derived from MOF are usually closely related to the structure and composition of the MOF precursor. At present, the morphology of the obtained MOF materials is still relatively small, usually rhombic dodecahedron, cube, rod and sheet, and the size is large, most of which are greater than 100 nm. The specific surface area used in the subsequent self-template construction of nanomaterials is relatively small, the ion diffusion path is relatively long, and most of the preparation methods are relatively complicated. Therefore, it is still necessary to design and study new simple and green synthesis strategies. Summary of the invention

[0005] The purpose of the present invention is to overcome the problems existing in the prior art and provide an imidazole-based MOF material and a preparation method and application thereof. The imidazole-based MOF material of the present invention is applied to the negative electrode of a lithium ion battery, which is beneficial to improving the electrochemical performance of the negative electrode material.

[0006] In order to achieve the above-mentioned object, the present invention provides an imidazole-based MOF material on one hand, wherein the MOF material has a nano-spherical morphology; the MOF material has an amorphous structure.

[0007] Preferably, the MOF material is a densely packed structure assembled from nano-spherical particles.

[0008] Preferably, the size of the nano-spherical particles is 50-120 nm.

[0009] Preferably, the number of nano-spherical particles with a size of 70-100 nm accounts for 70-80% of the total number of nano-spherical particles.

[0010] A second aspect of the present invention provides a method for preparing a MOF material, the method comprising the following steps: (1) allowing an organic ligand aqueous solution and a metal source precursor aqueous solution to react to obtain a solid product; (2) washing the solid product of step (1) and then drying it; The molar ratio of the organic ligand to the metal source precursor is 10-20.

[0011] The third aspect of the present invention provides an application of the imidazole-based MOF material described in the first aspect or the imidazole-based MOF material prepared by the method described in the second aspect in a lithium-ion battery.

[0012] Through the above technical solution, the beneficial effects of the present invention include: The MOF material of the present invention has a nano-spherical morphology and an amorphous structure. The nanomaterial derived from the MOF material as a self-template can provide a larger specific surface area, more coordination unsaturated sites, a shorter ion diffusion path, and alleviate microscopic volume expansion, so that the electrochemical performance of the negative electrode of the lithium-ion battery is improved. Preferably, the MOF material of the present invention has a specific size feature and is applied to lithium-ion batteries to further improve the mass specific capacity, rate performance and stability of the negative electrode material.

[0013] The preparation method of the present invention can obtain the MOF material with nano-spherical morphology and amorphous structure of the present invention by a one-step reaction method, which has simple process, mild conditions, green and environmental protection, and is suitable for wide application. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 is a SEM image of the MOF material prepared in Example 1 of the present invention; Figure 2 is the XRD pattern of the MOF material prepared in Example 1 of the present invention; Figure 3 is a SEM image of the MOF material prepared in Comparative Example 1 of the present invention; Figure 4 is a SEM image of the MOF material prepared in Comparative Example 3 of the present invention; Figure 5 It is a SEM picture of the MOF material prepared in Comparative Example 4 of the present invention. DETAILED DESCRIPTION

[0015] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0016] One aspect of the present invention provides an imidazole-based MOF material, wherein the MOF material has a nano-spherical morphology; the MOF material has an amorphous structure.

[0017] The spherical morphology of the MOF material of the present invention is measured by SEM.

[0018] The MOF materials in the prior art are usually rhombic dodecahedron, cube, rod or sheet, and are relatively large in size, mostly larger than 100 nm, and the specific surface area used in the subsequent self-template construction of nanomaterials is relatively small. The use of the MOF material with an amorphous structure and a nano-spherical morphology as a self-template derived nanomaterial can provide a larger specific surface area, more coordination unsaturated sites, a shorter ion diffusion path and alleviate microscopic volume expansion, so that the mass specific capacity, rate performance and stability of the negative electrode of the lithium-ion battery are improved.

[0019] It should be noted that the sphere described in the present invention may be a sphere in a narrow sense, or may be an incompletely regular sphere, such as a quasi-spherical shape.

[0020] The non-crystalline structure of the MOF material of the present invention is measured by XRD, indicating that amorphous MOF nanospheres are obtained.

[0021] According to the present invention, preferably, the metal element in the MOF material is zinc and / or cobalt. This preferred embodiment can achieve better coordination with the organic ligand molecule of the present invention.

[0022] According to the present invention, preferably, the organic ligand in the MOF material is selected from at least one of 2-methylimidazole, 4-methylimidazole and 2,4-dimethylimidazole.

[0023] According to the present invention, preferably, the organic ligand is 2-methylimidazole, and 4-methylimidazole and / or 2,4-dimethylimidazole, and the molar ratio of 2-methylimidazole to 4-methylimidazole and / or 2,4-dimethylimidazole is 1:0-0.25, preferably 1:0.05-0.2, for example, it can be 1:0, 1:0.05, 1:0.1, 1:0.15, 1:0.2, 1:0.25 and any value in the range formed by any two of these point values.

[0024] According to the present invention, preferably, the MOF material is a densely packed structure composed of nano-spherical particles. By adopting this preferred embodiment, the surface energy of the nano-spherical MOF material can be reduced.

[0025] The densely packed structure of the MOF material of the present invention can be seen by SEM, which can be referred to Figure 1 .from Figure 1 It can also be seen that the spherical particles of the MOF material have good dispersion and are basically non-adhesive, which can ensure that no significant agglomeration occurs in the nanomaterial derived from it as a self-template, resulting in a decrease in the specific surface area of ​​the material, thereby improving the lithium battery performance of the negative electrode material.

[0026] According to the present invention, preferably, the size of the nano spherical particles is 50-120 nm.

[0027] The size of the nano spherical particles of the present invention refers to the maximum straight-line distance between two points on the sphere. The size of the nano spherical particles of the present invention is measured by SEM.

[0028] According to the present invention, preferably, the number of nano-spherical particles with a size of 70-100 nm accounts for 70-80% of the total number of nano-spherical particles. This preferred size of MOF material is applied to the negative electrode of lithium-ion batteries, which is more conducive to improving the rate performance of the negative electrode material.

[0029] The size distribution of the nano-spherical particles of the present invention is measured by SEM and calculated by Nano Measurer 1.2 particle size statistics software, and the statistical base is 200 MOF nano-spheres in the SEM image.

[0030] The present invention has no particular limitation on the preparation method of the above-mentioned imidazole-based MOF material, as long as the imidazole-based MOF material with the above-mentioned composition and characteristics can be prepared. In order to further illustrate the advantages of the imidazole-based MOF material of the present invention, the present invention also provides a preparation method of the above-mentioned imidazole-based MOF material.

[0031] A second aspect of the present invention provides a method for preparing a MOF material, the method comprising the following steps: (1) allowing an organic ligand aqueous solution and a metal source precursor aqueous solution to react to obtain a solid product; (2) washing the solid product of step (1) and then drying it; The molar ratio of the organic ligand to the metal source precursor is 10-20.

[0032] The molar ratio of the organic ligand to the metal source precursor of the present invention is 10-20, preferably 13-19, for example, it can be 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1, 20:1 and any value in the range formed by any two of these point values. By adopting this preferred embodiment, a suitable MOF nucleation rate can be ensured to obtain the MOF material with spherical morphology and amorphous structure of the present invention.

[0033] When the number of the organic ligands is two or more, the molar amount of the organic ligands is the total molar amount of the two or more organic ligands.

[0034] Preferably, the reaction conditions of step (1) include: temperature of 20-35°C, preferably 24-28°C, for example, 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C, 30°C, 31°C, 32°C, 33°C, 34°C, 35°C and any value in the range formed by any two of these point values; time of 1-6h, preferably 2-4h, for example, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h and any value in the range formed by any two of these point values. By adopting this preferred embodiment, the nucleation rate and the degree of spherical morphology reaction can be controlled.

[0035] It should be noted that when the reaction time of step (1) exceeds 6 h, it will lead to hydrolysis of the amorphous MOF and disappearance of the spherical morphology.

[0036] In the present invention, the reaction process in step (1) is the process of crystal growth.

[0037] According to the present invention, preferably, before the standing reaction in step (1) is carried out, the organic ligand aqueous solution and the metal source precursor aqueous solution are first mixed.

[0038] According to the present invention, preferably, the mixing is performed under stirring conditions.

[0039] The present invention has no particular limitation on the stirring rate, which can be appropriately selected according to specific circumstances, as long as the purpose of uniform mixing can be achieved.

[0040] In the present invention, the mixing time is relatively short, generally only 2-5 minutes, and the mixing time is not included in the reaction time of step (1).

[0041] According to the present invention, preferably, the organic ligand is selected from at least one of 2-methylimidazole, 4-methylimidazole and 2,4-dimethylimidazole.

[0042] Further preferably, the organic ligand is 2-methylimidazole, and 4-methylimidazole and / or 2,4-dimethylimidazole, and the molar ratio of 2-methylimidazole to 4-methylimidazole and / or 2,4-dimethylimidazole is 1:0-0.25, preferably 1:0.05-0.2, for example, it can be 1:0, 1:0.05, 1:0.1, 1:0.15, 1:0.2, 1:0.25 and any value in the range formed by any two of these point values.

[0043] The inventors of the present invention discovered during the research process that the use of specific types of organic ligands in specific proportions is beneficial to regulating the initial nucleation rate of MOF, and is further beneficial to obtaining the MOF material with spherical morphology and amorphous structure as described in the present invention.

[0044] According to the present invention, preferably, the metal source precursor is a soluble salt of a metal source, preferably at least one selected from cobalt acetate, zinc chloride, cobalt nitrate, zinc nitrate, cobalt chloride and zinc acetate. The above substances are conventionally selected in the art and can be obtained commercially.

[0045] In the present invention, the "soluble" means that the compound can be dissolved in a solvent directly or with the help of a co-solvent.

[0046] According to the present invention, preferably, the concentration of the organic ligand aqueous solution is 0.1-0.6 mol / L, preferably 0.3-0.5 mol / L.

[0047] When the number of the organic ligands is two or more, the concentration of the organic ligand aqueous solution is the total concentration of the two or more organic ligands.

[0048] According to the present invention, preferably, the concentration of the metal source precursor aqueous solution is 5-30 mg / mL, preferably 5-10 mg / mL.

[0049] The present invention has no particular limitation on the specific preparation process of the organic ligand aqueous solution and the metal source precursor aqueous solution, which can be carried out under ultrasonic or stirring conditions. The present invention has no particular limitation on this.

[0050] Preferably, the reaction product of step (1) is separated to obtain a solid product.

[0051] The present invention has no particular limitation on the separation method, which can be carried out using conventional technical means in the art and is not limited herein.

[0052] Preferably, the washing agent in step (2) is an organic solvent, and the organic solvent is a C1-C6 alcohol, preferably at least one selected from methanol, ethanol and isopropanol. This preferred embodiment can avoid the hydrolysis reaction of the amorphous MOF during the washing process.

[0053] The present invention has no particular limitation on the drying conditions in step (2), and the drying can be carried out according to conventional methods in the art. According to the present invention, preferably, the drying conditions in step (2) include: a temperature of 40-60° C. and a drying time of 2-24 h.

[0054] The drying of the present invention can be carried out under vacuum, under low pressure, or under normal pressure. Preferably, the drying in step (2) is carried out under vacuum.

[0055] According to the method provided by the present invention, preferably, the MOF material has a nano-spherical morphology.

[0056] According to the method provided by the present invention, preferably, the MOF material has an amorphous structure.

[0057] According to the method provided by the present invention, preferably, the MOF material is a densely packed structure assembled from nano-spherical particles.

[0058] According to the method provided by the present invention, preferably, the size of the nano-spherical particles is 50-120 nm.

[0059] According to the method provided by the present invention, preferably, the number of nano spherical particles with a size of 70-100 nm accounts for 70-80% of the total number of nano spherical particles.

[0060] According to a particularly preferred embodiment of the present invention, a method for preparing a MOF material comprises the following steps: (1) allowing an organic ligand aqueous solution and a metal source precursor aqueous solution to react to obtain a solid product; (2) washing the solid product of step (1) and then drying it; The molar ratio of the organic ligand to the metal source precursor is 13-19; The reaction conditions of step (1) include: temperature of 24-28°C and time of 2-4h; The organic ligand is 2-methylimidazole, 4-methylimidazole and / or 2,4-dimethylimidazole, and the molar ratio of 2-methylimidazole to 4-methylimidazole and / or 2,4-dimethylimidazole is 1:0.05-0.2; The MOF material has a nano-spherical morphology; The MOF material has an amorphous structure; The size of the nano spherical particles is 50-120 nm; The number of nano-spherical particles with a size of 70-100 nm accounts for 70-80% of the total number of nano-spherical particles.

[0061] By adopting the above preferred implementation mode, the prepared MOF material can be applied to lithium-ion batteries, which is further beneficial to improving the electrochemical performance of the negative electrode material.

[0062] The third aspect of the present invention provides an application of the imidazole-based MOF material described in the first aspect or the imidazole-based MOF material prepared by the method described in the second aspect in a lithium-ion battery, preferably in a negative electrode of a lithium-ion battery.

[0063] The present invention will be described in detail below through examples.

[0064] In the following examples, SEM test: The present invention uses a scanning electron microscope of model Hitachi S-4800, with an operating voltage of 5 kV-20 kV and equipped with energy dispersive X-ray spectroscopy (EDS); XRD test: This method uses an X-ray diffractometer model XRD-6000 produced by Shimadzu, Japan. The test conditions include: tube voltage 40 kV, tube current 40 mA, Cu target Kα radiation, 2θ scanning range 5°-70°, and scanning speed 5° / min.

[0065] Example 1 (1) Dissolve an appropriate amount of 2-methylimidazole and 4-methylimidazole organic ligands (the molar ratio of 2-methylimidazole to 4-methylimidazole is 1:0.1) in water and stir to obtain an organic ligand aqueous solution with a total concentration of 0.4 mol / L. Dissolve an appropriate amount of cobalt nitrate metal source precursor in water and stir to obtain a cobalt nitrate aqueous solution with a concentration of 7.275 mg / mL. Mix the above organic ligand aqueous solution and the cobalt nitrate aqueous solution (the total molar ratio of the organic ligand to the molar ratio of the metal source precursor is 16:1) and stir for 3 minutes to obtain a mixed solution. Place the above mixed solution in a static environment at a constant temperature of 27°C for 3 hours to grow crystals to obtain a material containing MOF.

[0066] (2) The material containing MOF was centrifuged and washed with ethanol in sequence, and then vacuum dried at 50°C for 12 hours to obtain MOF material. The characterization results of the MOF material are listed in Table 1 below.

[0067] The SEM image of the MOF material prepared in Example 1 is shown as an example. Figure 1 .from Figure 1 It can be seen that the MOF material is a densely packed structure assembled from nano-spherical particles; the spherical particles of the MOF material have good dispersion and basically no adhesion; the surface of the nanospheres is relatively smooth, and the lithium-ion battery negative electrode material constructed using them as a self-template has good dispersion, and is also beneficial to alleviate the volume expansion problem during the charge and discharge process, thereby improving the electrochemical performance of the negative electrode material.

[0068] The XRD spectrum of the MOF material prepared in Example 1 is shown in FIG. Figure 2 .from Figure 2 It can be seen that the XRD spectrum does not show a significant diffraction peak in the range of 10-70°, indicating that the MOF material of the present invention has a non-crystalline structure, thereby indicating that an amorphous MOF material is obtained.

[0069] Example 2 (1) Dissolve an appropriate amount of two organic ligands, 2-methylimidazole and 2,4-dimethylimidazole (the molar ratio of 2-methylimidazole to 2,4-dimethylimidazole is 1:0.2) in water and stir to obtain an organic ligand aqueous solution with a total concentration of 0.35 mol / L. Dissolve an appropriate amount of zinc nitrate metal source precursor in water and stir to obtain an aqueous zinc nitrate solution with a concentration of 7.275 mg / mL. Mix the above 2-methylimidazole aqueous solution and zinc nitrate aqueous solution (the total molar ratio of organic ligand to metal source precursor is 14:1) and stir for 5 minutes to obtain a mixed solution. Place the above mixed solution in a static environment at a constant temperature of 25°C for 4 hours to allow crystals to grow to obtain a material containing MOF.

[0070] (2) The material containing MOF was centrifuged and washed with methanol in sequence, and then vacuum dried at 60°C for 20 hours to obtain MOF material. The characterization results of the MOF material are listed in Table 1 below.

[0071] The SEM images of the MOF material prepared in Example 2 are Figure 1 Similarly, it is shown that the MOF material has a spherical morphology.

[0072] The XRD spectrum of the MOF material prepared in Example 2 is Figure 2 similar.

[0073] Comparative Example 1 The method of Example 1 was followed, except that the crystal growth process in step (1) was not carried out in a static environment, but was carried out under stirring conditions at 350 rpm to obtain a MOF material. The characterization results of the MOF material are listed in Table 1 below.

[0074] The SEM image of the MOF material obtained in Comparative Example 1 is shown in Figure 3 .from Figure 3 It can be seen that the MOF material mainly presents a shuttle-shaped nanorod morphology, and its surface is covered with some nano-spherical MOFs.

[0075] Comparative Example 2 The method of Example 1 was followed, except that an appropriate amount of 2-methylimidazole and 4-methylimidazole organic ligands were dissolved in methanol and stirred to obtain an organic ligand methanol solution with a total concentration of 0.4 mol / L. An appropriate amount of cobalt nitrate was dissolved in methanol and stirred to obtain a cobalt nitrate methanol solution with a concentration of 7.275 mg / mL, and finally a typical MOF material with a dodecahedral morphology was obtained. The characterization results of the MOF material are listed in Table 1 below.

[0076] Comparative Example 3 The method of Example 1 was followed, except that the total molar amount ratio of the organic ligand to the metal source precursor in step (1) was 8:1, to obtain a MOF material. The characterization results of the MOF material are listed in Table 1 below.

[0077] The SEM image of the MOF material obtained in Comparative Example 3 is shown in Figure 4 .from Figure 4 It can be seen that the MOF material of Comparative Example 3 shows the morphology of micro-nano blades.

[0078] Comparative Example 4 (1) Dissolve an appropriate amount of 2-methylimidazole and 4-methylimidazole organic ligands (the molar ratio of 2-methylimidazole to 4-methylimidazole is 1:0.1) in water and stir to obtain an organic ligand aqueous solution with a total concentration of 0.4 mol / L. Dissolve an appropriate amount of cobalt nitrate metal source precursor in water and stir to obtain a cobalt nitrate aqueous solution with a concentration of 14.5 mg / mL. Mix the above organic ligand aqueous solution and the cobalt nitrate aqueous solution (the total molar ratio of the organic ligand to the molar ratio of the metal source precursor is 8:1) and stir for 3 minutes to obtain a mixed solution. Place the above mixed solution at room temperature 25°C and stir at 350 rpm for 3 hours to grow crystals to obtain a material containing MOF.

[0079] (2) The material containing MOF was centrifuged and washed with water in sequence, and then vacuum dried at 50°C for 12 hours to obtain MOF material. The characterization results of the MOF material are listed in Table 1 below.

[0080] The SEM image of the MOF material obtained in Comparative Example 4 is shown in Figure 5 .from Figure 5 It can be seen that the MOF material of Comparative Example 4 shows the morphology of micro-nano blades.

[0081] Table 1 It can be seen from the results in Table 1 that the method of the present invention is conducive to preparing the MOF material having a spherical morphology and an amorphous structure of the present invention.

[0082] Compared with the MOF material obtained in the comparative example, the MOF material of the present invention can provide a larger specific surface area, more coordination unsaturated sites, and a shorter ion diffusion path, while effectively alleviating microscopic volume expansion. It is inferred that the use of the MOF material of the present invention in lithium-ion batteries can further improve the electrochemical performance of the negative electrode material.

[0083] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. An imidazole-based MOF material, characterized in that: The MOF material has a nano-spherical morphology; the MOF material has an amorphous structure.

2. The MOF material according to claim 1, wherein The metal elements in the MOF material are zinc and / or cobalt; The organic ligand in the MOF material is selected from at least one of 2-methylimidazole, 4-methylimidazole and 2,4-dimethylimidazole; Preferably, the organic ligand is 2-methylimidazole, and 4-methylimidazole and / or 2,4-dimethylimidazole, and the molar ratio of 2-methylimidazole to 4-methylimidazole and / or 2,4-dimethylimidazole is 1:0-0.25, preferably 1:0.05-0.

2.

3. The MOF material according to claim 1 or 2, wherein: The MOF material is a densely packed structure assembled from nano-spherical particles; Preferably, the size of the nano-spherical particles is 50-120 nm; Preferably, the number of nano-spherical particles with a size of 70-100 nm accounts for 70-80% of the total number of nano-spherical particles.

4. A method for preparing a MOF material, the method comprising the following steps: (1) allowing an organic ligand aqueous solution and a metal source precursor aqueous solution to react to obtain a solid product; (2) washing the solid product of step (1) and then drying it; The molar ratio of the organic ligand to the metal source precursor is 10-20.

5. The method according to claim 4, wherein: The molar ratio of the organic ligand to the metal source precursor is 13-19; Preferably, the reaction conditions in step (1) include: temperature of 20-35°C, preferably 24-28°C; time of 1-6h, preferably 2-4h; Preferably, before the standing reaction in step (1) is carried out, the organic ligand aqueous solution and the metal source precursor aqueous solution are first mixed; Preferably, the mixing is performed under stirring conditions.

6. The method according to claim 4, wherein: The organic ligand is selected from at least one of 2-methylimidazole, 4-methylimidazole and 2,4-dimethylimidazole; Preferably, the organic ligand is 2-methylimidazole, and 4-methylimidazole and / or 2,4-dimethylimidazole, and the molar ratio of 2-methylimidazole to 4-methylimidazole and / or 2,4-dimethylimidazole is 1:0-0.25, preferably 1:0.05-0.2; Preferably, the metal source precursor is a soluble salt of a metal source, preferably at least one selected from the group consisting of cobalt acetate, zinc chloride, cobalt nitrate, zinc nitrate, cobalt chloride and zinc acetate.

7. The method according to any one of claims 4 to 6, wherein: The concentration of the organic ligand aqueous solution is 0.1-0.6 mol / L, preferably 0.3-0.5 mol / L; Preferably, the concentration of the metal source precursor aqueous solution is 5-30 mg / mL, preferably 5-10 mg / mL.

8. The method according to any one of claims 4 to 7, wherein: The washing agent used in step (2) is an organic solvent, and the organic solvent is selected from at least one of methanol, ethanol and isopropanol.

9. The method according to any one of claims 4 to 8, wherein: The MOF material has a nano-spherical morphology; Preferably, the MOF material has an amorphous structure; Preferably, the MOF material is a densely packed structure assembled from nano-spherical particles; Preferably, the size of the nano-spherical particles is 50-120 nm; Preferably, the number of nano-spherical particles with a size of 70-100 nm accounts for 70-80% of the total number of nano-spherical particles.

10. Use of the imidazole-based MOF material according to any one of claims 1 to 3 or the imidazole-based MOF material obtained by the method according to any one of claims 4 to 9 in a lithium-ion battery, preferably in a negative electrode of a lithium-ion battery.

Citation Information

Patent Citations

  • Amorphous MOF nano photosensitizer as well as preparation method and application thereof

    CN114790218A

  • Preparation method of ZIF-8 and glutathione response type hollow microspheres

    CN115260508A

  • Amorphous cobalt oxide / carbon / metal organic framework composite material and preparation method and application thereof

    CN115483381A